Do Individuals with Alcohol Dependence Show Higher Unfairness Sensitivity? The Relationship Between Impulsivity and Unfairness Sensitivity in Alcohol‐Dependent Adults. (1st September 2015) - Tsukue, Ryotaro; Okamoto, Yasumasa; Yoshino, Atsuo; Kunisato, Yoshihiko; Takagaki, Koki; Takebayashi, Yoshitake; Tanaka, Keisuke; Konuma, Kyohei; Tsukue, Ichiro; Yamawaki, Shigeto
<x xml:space="preserve">Abstract</x> Background Alcohol‐dependent patients are known to be generally more unfairness sensitive. The ultimatum game (UG) is an experimental task designed to provoke feelings of perceived unfairness. A previous study using the UG has reported more unfairness sensitivity in patients with alcohol dependence than in a nondependent control group; it has been speculated that this increased sensitivity might be due to a difficulty in impulse control. However, the mechanism of this relationship has not been clarified. Therefore, the relationship between unfairness sensitivity in interpersonal relationships and impulsivity was investigated using UG and delay discounting (DD) paradigms. Methods Subjects were 32 individuals with alcohol dependency and 36 healthy control individuals; both groups performed UG and DD tasks. Results Participants with alcohol dependence rejected monetary offers deemed unfair at a significantly higher rate than did control participants. Moreover, the proportion of accepting unfairness was negatively correlated with impulsivity in patients with alcohol dependence. Conclusions Perceived unfairness is related to impulsivity in patients with alcohol dependence. These results provide insights concerning the psychopathology of alcohol dependence.